KETERLIBATAN PERPUSTAKAAN KEMENTERIAN PERTANIAN DALAM PENGELOLAAN INFORMASI PUBLIK - Rushendi Rushendi; Ceria Isra Ningtiyas (Perpustakaan Nasional RI, 2019)
The act No.14 of 2008 on Publict Information Openness is the government’s effort to organize and manage publict information more efficiently so that it is easy for the public to access information. Proffesional publict information management is an effort to develop information services for the publict. The library as a publict agency unit has duties to manage and to serve information request from the publict, as well as to cooperate with publict information services, PIO ( Publict Information Officer). The aim of the study was to find out the involvement of Ministry of Agriculture library in the management of publict information. This study was conducted from February to May 2018 using quantitative descriptive method data of 48 librarians / library staff as respondents. The variables observed include Respondent’s Involvement Level and Respondent’s Competency Level. The variables data were collected by survey method using Google from questionnare https://docs.google.com/forms distributed to each respondent throught Rank Sperman’s correlation test. The result show that half of the respondents were female with age 30-50 years old. Most of them were pustakawan ahli pertama (first expers librarian) who had 10 years of services and were mostly from Research Centre, Research Institute and AIAT (Assesment Institute for Agriculture Technology). Almost all libraries are involved in PIO activities. The involvment of the librarian / librari staffs to PIO at the level of knowledge, understanding and expertise was relatively high; but tended to be standard in behaviour. Based on spearmen’s correlation test, there is a significant correlation between the competence of librarian/library staff and the involvement in PIO. The role of PIO should be more developed through socialization, workshop and training of PIO in Ministryof Agriculture.